A New Art of Dying as a Cultural Challenge. (August 2016) - Leget, Carlo
In North Atlantic culture dying is mostly seen as a personal event. The societal dimension of dying and the impact of the cultural horizon are often overlooked. In this contribution a revised version of a medieval Ars moriendi model is used as a lens to perceive the one-sidedness of North Atlantic culture.